Patient-Centered Outcomes After Modified Vestibulectomy. Issue 1 (January 2020) - Das, Deepanjana; Davidson, Emily R. W.; Walters, Mark; Farrell, Ruth M.; Ferrando, Cecile A.
Abstract : OBJECTIVE: To describe patient outcomes after modified vestibulectomy for vulvodynia. METHODS: This is a mixed-methods study of patients who had undergone modified vestibulectomy for vulvodynia at a tertiary care hospital from 2009 through 2016. Demographics, preoperative and postoperative examinations, symptoms, and treatments were obtained through retrospective review. Prospective semistructured interviews were conducted from 2018 through 2019 to address patient-reported changes in pain and sexual function. Qualitative analysis was performed using a grounded theory approach. RESULTS: Twenty-two patients underwent modified vestibulectomy from 2009 through 2016. Age ranged from 22 to 65 years and mean body mass index was 24.3±5.4. The majority of patients were premenopausal (57%), sexually active (68%), and partnered (76%). Postoperatively, data on pain improvement were retrieved on 18 patients, of which 17 (94%) reported improvement. Patients used pelvic floor physical therapy, medications, and lubricants both preoperatively and postoperatively. For the qualitative analysis, thematic saturation was achieved with 14 interviews. Of 14 participants interviewed, 13 (93%) reported improvement with pain after surgery, 11 (79%) reported satisfaction with surgery, 8 (57%) reported satisfaction with sexual function, and 11 (79%) reported recommending the surgery to others. The following lead themes were identified: vulvodynia symptoms significantly affect quality of life; there is difficulty and delay in diagnosis owing to lack of information and awareness among patients and health care providers; and surgical success and satisfaction are influenced by patient perceptions with sexual dysfunction often persisting despite vulvar pain improvement. CONCLUSION: Vulvodynia patients report improvement in pain and high overall satisfaction after modified vestibulectomy, but more variable long-term effects on sexual function. Abstract : Vulvodynia is a complex pain condition requiring a patient-specific and multimodal approach to management before and after modified vestibulectomy.